Benefit-risk evaluation of Fuzheng Yiliu Decoction combined with chemotherapy for treating non-small cell lung cancer using multicriteria decision analysis - Ma, Dongjing; Yang, Yingying; He, Shenwen; Gao, Keqin; Wang, Jinbin; Yan, Di; Zhang, Yuanchao; Wu, Jianjun (Frontiers in Oncology, 2025)
IntroductionThis study uses multi-criteria decision analysis (MCDA) to evaluate the benefits and risks of combining Fuzheng Yiliu Decoction with chemotherapy in treating non-small cell lung cancer (NSCLC). The aim is to improve clinical outcomes for NSCLC patients by integrating traditional Chinese medicine with conventional chemotherapy.MethodsA comprehensive literature search was conducted in PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), China Biology Medicine Disc (CBM), Wanfang Databases, and China Science and Technology Journal Database (VIP Databases) to identify relevant studies on Fuzheng Yiliu Decoction combined with chemotherapy for NSCLC. Meta-analysis using RevMan 5.3 was performed to compare the effect sizes of the two treatment regimens. A MCDA model was developed to construct a value tree based on benefit-risk indicators. The benefit value, risk value, and benefit-risk ratio for both treatments were calculated using Hiview 3.2 software, followed by sensitivity analysis to assess result robustness. Monte Carlo simulations were performed using Oracle Crystal Ball 11.1 software to optimize the evaluation outcomes.ResultsThe literature search identified 6 randomized controlled trials (RCTs) comparing chemotherapy alone with chemotherapy combined with Fuzheng Yiliu Decoction. The MCDA model showed that the combination therapy had significantly higher benefit values (72) compared to chemotherapy alone (29). The risk value for combination therapy (56) was slightly higher than that of chemotherapy alone (24), but the overall benefit-risk value for combination therapy (68) was notably greater than chemotherapy alone (27). Monte Carlo simulations revealed a difference in total efficacy-risk values between the two treatments of 41 (95% CI: -16.59, 38.73). The probability that the combination therapy’s benefit-risk value exceeds that of chemotherapy alone was 81.83%.DiscussionThese findings suggest that combining Fuzheng Yiliu Decoction with chemotherapy improves therapeutic efficacy and reduces chemotherapy’s adverse side effects, offering a promising treatment strategy for NSCLC. This study provides valuable insights into enhancing treatment strategies and clinical decision-making in managing NSCLC.